Digital healthcare services in community pharmacies in Switzerland: Pharmacist and patient acceptability, and pharmacist readiness–the Pneumoscope™ pilot study - Claudine Backes; Coralie Godot; Cédric Yan Gujer; Noémie Obegi; Alexandre Perez; Alain Gervaix; Marie P. Schneider (Digital Health)
Background The integration of artificial intelligence (AI)-based pharmaceutical services in community pharmacy (CP) settings has the potential to enhance point-of-care services and improve informed patient access to healthcare. The Pneumoscope™, an innovative AI-powered digital stethoscope that analyses lung sounds to detect specific respiratory pathologies, could be a valuable tool for pharmacists in conducting respiratory screening. To understand how this device can be implemented in the healthcare system, this exploratory research aims to assess the acceptability of pharmacists and patients, and the pharmacists’ readiness to use the Pneumoscope™ in CPs for respiratory disease management. Methods A 2-stage exploratory approach was conducted using mixed methods: 1) a qualitative analysis of pharmacists’ acceptability and readiness was developed using semi-structured interviews and focus groups ; 2) followed by a quantitative cross-sectional survey of patients’ acceptability of the device in CPs. Results Pharmacists were generally positive about the integration of e-health services into their daily clinical practice, recognizing their potential to improve advanced pharmaceutical triage and collaboration with physicians. Most patients were satisfied with the care provided by CPs, and their acceptability to use the Pneumoscope™ was significantly associated with their level of confidence in AI (p = 0.0092) and with the location of their CP (p = 0.0276). Conclusions Digital devices such as the Pneumoscope™ have the potential to reinforce the pharmacists’ clinical roles within an interprofessional team and improve patient care, but further scientific evaluation and implementation are necessary to support its integration and ensure its reimbursement by health insurers.